Unresolved drooling in a previously healthy child caused by a brainstem malignancy - Shelton, Fenella; Sproson, Eleanor; Van der Veen, Jana; Evans, Hazel; Burgess, Andrea; Ismail-Koch, Hasnaa (International journal of pediatric otorhinolaryngology, 2017)
Drooling occurs commonly in children below the age of two. In a small group of children this persists and an otorhinolaryngology consultation is sought. In children with no neurological abnormality or comorbidity, reassurance and behavioural management is often suggested. We present a case where drooling was the presenting feature of brain stem malignancy. Diagnosis was suggested following a sleep study demonstrating central apnoeas. Magnetic resonance imaging (MRI) showed an intra-axial brainstem tumour. This case highlights the importance of multidisciplinary team (MDT) management of children with persistent drooling of unknown cause.